Development of a Project-Based Learning Model Using Science Games to Enhance Social Skills in Early Childhood: PjBL Model, Science based game, Social skills - huda, khairulhuda; Sofia Hartati; Ade Dwi Utami (Sekolah Pascasarjana Universitas Negeri Jakarta, 2024)
This study examines the effectiveness of project-based learning (PBL) using science-themed games in early childhood education. Through a qualitative research approach, the study explores how integrating science games within the PBL framework can enhance children's social skills. It identifies the importance of engaging children in science-themed projects to foster responsibility, cooperation, active participation, communication, sharing, and adaptability from an early age. By analyzing participants' responses and learning outcomes, the study highlights the potential benefits of this approach, including improved collaboration and adaptability skills among young children. The findings suggest that science-themed project-based learning enriches educational experiences and plays a crucial role in shaping socially skilled future generations.